Autoantibodies as biomarkers for breast cancer diagnosis and prognosis - Yang, Ruozhu; Han, Yi; Yi, Wenjun; Long, Qian (Frontiers in Immunology, 2022)
Breast cancer is the most common cancer in women worldwide and is a substantial public health problem. Screening for breast cancer mainly relies on mammography, which leads to false positives and missed diagnoses and is especially nonsensitive for patients with small tumors and dense breasts. The prognosis of breast cancer is mainly classified by tumor, node, metastasis (TNM) staging, but this method does not consider the molecular characteristics of the tumor. As the product of the immune response to tumor-associated antigens, autoantibodies can be detected in peripheral blood and can be used as noninvasive, presymptomatic, and low-cost biomarkers. Therefore, autoantibodies can provide a possible supplementary method for breast cancer screening and prognosis classification. This article introduces the methods used to detect peripheral blood autoantibodies and the research progress in the screening and prognosis of breast cancer made in recent years to provide a potential direction for the examination and treatment of breast cancer.